Pharmacokinetics of salvianolic acid B, rosmarinic acid and Danshensu in rat after pulmonary administration of Salvia miltiorrhiza polyphenolic acid solution. (10th May 2019) - Lu, Peng; Xing, Yue; Xue, Zhifeng; Ma, Zhe; Zhang, Bing; Peng, Hui; Zhou, Qi (Tony); Liu, Hongfei; Liu, Zhidong; Li, Jiawei
Abstract: A sensitive and accurate LC–MS/MS method was established for quantifying salvianolic acid B (Sal B), rosmarinic acid (Ros A) and Danshensu (DA) in rat plasma. Salvia miltiorrhiza polyphenolic acid (SMPA), active water‐soluble ingredients isolated and purified from Salvia miltiorrhiza Bge included Sal B, Ros A and DA. The pharmacokinetic analysis of Sal B, Ros A and DA after pulmonary administration of SMPA solution to rat was performed by LC–MS/MS. Results from the pharmacokinetic studies showed that the peak concentration of DA was 21.85 ± 6.43 and 65.39 ± 3.83 ng/mL after pulmonary and intravenous administration, respectively. DA was not detected at 2 h after administration. The absolute bioavailabilities of Sal B and Ros A were respectively 50.37 ± 27.04 and 89.63 ± 12.16% after pulmonary administration of 10 mg/kg SMPA solution in rats. The absolute bioavailability of Sal B increased at least 10‐fold after pulmonary administration, compared with oral administration. It was concluded that the newly established LC–MS/MS method was suitable for describing the pharmacokinetic characteristics of Sal B, Ros A and DA in rat after pulmonary administration of SMPA solution. The data from this study will provide a preclinical insight into the feasibility of pulmonary administration of SMPA.